PROCESSES OF REALIZATION OF KARAKALPAK FOLKLORE IN SYMPHONIC MUSIC OF 30-80 YEARS OF XX- CENTURY - Jamil Charshemov (Web of Journals Publishing, 2024)
The aim of this article is to reveal the originality of Karakalpak composers approaches to folklore, comparing their methods and techniques with those of their predecessors and contemporaries in other national schools, separating individuality from the typological features of the school and species features of the direction.
Keywords: Symphony, symphonic music, symphonietta, composer, orchestra, genre, melody, zhyrau, folklore.